Cognitive outcomes in patients with essential tremor treated with deep brain stimulation: a systematic review - Al Ali, Jamal; Lacy, Maureen; Padmanaban, Mahesh; Abou Chaar, Widad; Hagy, Hannah; Warnke, Peter C.; Xie, Tao (Frontiers in Human Neuroscience, 2024)
Introduction: Essential tremor (ET) is a common neurological disease. Deep brain stimulation (DBS) to the thalamic ventral intermediate nucleus (VIM) or the adjacent structures, such as caudal zona incerta/ posterior subthalamic area (cZi/PSA), can be effective in treating medication refractory tremor. However, it is not clear whether DBS can cause cognitive changes, and in which domain and to what extent if so. Methods: We systematically searched the PubMed and the Web of Science for available publications reporting on cognitive outcomes in patients with ET who underwent DBS following PICO concept. The PRISMA guideline for systematic reviews was applied. Results: Twenty relevant articles were finally identified and included for review, thirteen of which were prospective (one also randomized) studies, and seven were retrospective. Cognitive outcomes included attention, memory, executive function, language, visuospatial function, and mood related variables. VIM and cZi/PSA DBS were generally well tolerated, although verbal fluency and language production were affected in some patients. Additionally, left sided VIM DBS was associated with negative effects on verbal abstraction, word recall, and verbal memory performance in some patients. Conclusion: Significant cognitive decline after VIM or cZi/PSA DBS in ET patients appears to be rare. Future prospective randomized controlled trials are needed to meticulously study the effect of the location, laterality and stimulation parameters of the active contacts on cognitive outcomes, while considering possible medication change post DBS, timing, standard neuropsychological battery, practice effects, timing of assessment and effect size as potential confounders.